Armenia: an Uneasy Choice Between Russia's New Initiatives and the EU Eastern Partnership - M. Y. Vardazaryan (Vestnik MGIMO-Universiteta)
The article studies the problems of foreign policy orientations of the Republic of Armenia, first of all those concerning "Russian" and "European" integration processes. Particularly, the main stages and peculiarities of Armenia's cooperation with the EU are presented. The author reflects upon the issue of the essence of the status and perspectives of associated membership in the EU. Revealing the difficulties within the EU and on the CIS territory, the author analyzes the capabilities of Armenia to combine, on the one hand, economic integration with the West and, on the other, military-political integration with the East. The article identifies the reasons of "freezing" Armenian-Russian relations in early 2013. Examining the perspectives of the Association Agreement with the EU and of membership in the Customs Union and taking into account the complex geopolitical situation in the region, analyzing all the facets of Armenia's economic and political collaboration both with the EU and RF, the author comes to the conclusion that Yerevan's choice of September 35 3,2013 is expedient and justified. Deepened strategic cooperation with Moscow, first of all, provides military and energy security of Armenia, although the economic factor shouldn't be underestimated. The author draws attention to the fact that Armenia's involvement in the Customs Union avails it the opportunity to keep collaborating with the European Union, however, from a more powerful position, which we have already witnessed through the alterations in the tone of some European officials.